2020
DOI: 10.1111/jocd.13369
|View full text |Cite
|
Sign up to set email alerts
|

Study of efficacy of microneedling and mesoneedling in the treatment of epidermal melasma: A pilot trial

Abstract: Background: Melasma is a difficult to treat pigmentation disorder. However, some successes have been attained by microneedling. The aim of the present study was to evaluate the efficacy of microneedling using meso-depigmentation solution (mesoneedling) in comparison with standard microneedling, over a 4-month treatment period.Methods: As a part of this pilot study, 20 patients received microneedling on one side and mesoneedling on another side of their face. Treatment was repeated on a monthly basis for 4 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…There were 11 articles evaluating efficacy of combination of microneedling with other topical treatments, including TA (6 articles), TCC, mesotherapy, 20% vitamin C solution, depigmenting serum (rucinol, and sophora‐alpha), and PRP 36‐46 . Combination therapy showed significantly superior efficacy in five studies 36‐39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 11 articles evaluating efficacy of combination of microneedling with other topical treatments, including TA (6 articles), TCC, mesotherapy, 20% vitamin C solution, depigmenting serum (rucinol, and sophora‐alpha), and PRP 36‐46 . Combination therapy showed significantly superior efficacy in five studies 36‐39 .…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45][46] Combination therapy showed significantly superior efficacy in five studies. [36][37][38][39] Two studies demonstrated significantly more improvement with combination of microneedling and topical TA in comparison with microneedling alone or combined of sham device and topical TA. 36,37 In two other studies, there was no significant differences in efficacy of treatment between patients treated with combination of FCO 2 laser with 2% HQ or topical TA in comparison with 2% HQ alone, or microneedling with topical TA, respectively.…”
Section: Combination Of Microneedling With Topical Treatment Modalitiesmentioning
confidence: 99%
“…26 They found both of the methods as efficient to treat it; however, they did not compare each other. 26 A case series showed after the use of topical vitamin C serum during the microneedling F I G U R E 3 A, Before, and B. 2 wk after the 5th session (B) (A) sessions induced granulomas.…”
Section: Mesotherapymentioning
confidence: 98%
“…There is only one report evaluating both microneedling and mesoneedling for epidermal melasma in the literature. 26 They found both of the methods as efficient to treat it; however, they did not compare each other. 26 A case series showed after the use of topical vitamin C serum during the microneedling F I G U R E 3 A, Before, and B.…”
Section: Mesotherapymentioning
confidence: 98%
“…the breakdown time is reduced and the healing process is accelerated. 15 It also induces matrix metalloproteinases, thereby reducing hyperpigmentation (Menon). In general, the efficiency, safety, and ease of use make microneedling a suitable treatment option.…”
Section: Masi Scoring Was Usedmentioning
confidence: 99%